Psychological and family factors associated with suicidal ideation in pre-adolcscents. - Ros, Claudia; Canals, Josepa; Domènech-llabeira, Edelmira; Gras, Mª Eugenia; Viñas, Ferrán (The Spanish Journal of Psychology, 2002)
Sin resumen